Water use strategies of two co‐occurring tree species in a semi‐arid karst environment. Issue 4 (5th March 2013) - Swaffer, Brooke A.; Holland, Kate L.; Doody, Tanya M.; Li, Chris; Hutson, John
Abstract The flow of precipitation from the surface through to groundwater in karst systems is a complex process involving storage in the unsaturated zone and diffuse and preferential recharge pathways. The processes associated with this behaviour are not well understood, despite the prevalence of karst aquifers being used as freshwater supplies. As a result, uncertainty regarding the ecohydrological processes in this geological setting remains large. In response to the need to better understand the impact of woody vegetation on groundwater recharge, annual evapotranspiration (ET) rates and tree water sources were measured for two years above a shallow, fresh karst aquifer. Water use strategies of the co‐occurring Eucalyptus diversifolia subsp. diversifolia Bonpl. and Allocasuarina verticillata (Lam.) L. Johnson were investigated using a monthly water balance approach, in conjunction with measurement of the stable isotopes of water, leaf water potentials and soil matric potentials. The results suggest that it is unlikely groundwater resources are required to sustain tree transpiration, despite its shallow proximity to the soil surface, and that similarities exist between ET losses and the estimated long‐term average rainfall for this area. Irrespective of stand and morphological differences, E. diversifolia and A. verticillata ET rates showed remarkable convergence, demonstrating the ability of these co‐occurring species to maximise their use of the available precipitation, which avoids the requirement to differentiate between these species when estimating ET at a landscape scale. We conclude that the water holding capacity of porous geological substrates, such as those associated with karst systems, will play an important role in equilibrating annual rainfall variability and should be considered when assessing ecohydrological links associated with karst systems. Copyright © 2013 John Wiley & Sons, Ltd.